Boundedness and Asymptotic Stability of Multistep Methods for Generalized Pantograph Equations (Journal of Computational Mathematics, 2004)
In this paper, we deal with the boundedness and the asymptotic stability of linear and one-leg multistep methods for generalized pantograph equations of neutral type, which arise from some fields of engineering. Some criteria of the boundedness and the asymptotic stability for the methods are obtained.
Keywords: Boundedness; Asymptotic stability; Multistep methods; Generalized pantograph equations.